Factors impacting employment for people with autism spectrum disorder: A scoping review. (May 2019) - Scott, Melissa; Milbourn, Ben; Falkmer, Marita; Black, Melissa; Bӧlte, Sven; Halladay, Alycia; Lerner, Matthew; Taylor, Julie Lounds; Girdler, Sonya
The aim of this study is to holistically synthesise the extent and range of literature relating to the employment of individuals with autism spectrum disorder. Database searches of Medline, CINAHL, PsychINFO, Scopus, ERIC, Web of Science and EMBASE were conducted. Studies describing adults with autism spectrum disorder employed in competitive, supported or sheltered employment were included. Content analysis was used to identify the strengths and abilities in the workplace of employees with autism spectrum disorder. Finally, meaningful concepts relating to employment interventions were extracted and linked to the International Classification of Functioning, Disability and Health Core Sets for autism spectrum disorder. The search identified 134 studies for inclusion with methodological quality ranging from limited to strong. Of these studies, only 36 evaluated employment interventions that were coded and linked to the International Classification of Functioning, Disability and Health, primarily focusing on modifying autism spectrum disorder characteristics for improved job performance, with little consideration of the impact of contextual factors on work participation. The International Classification of Functioning, Disability and Health Core Sets for autism spectrum disorder are a useful tool in holistically examining the employment literature for individuals with autism spectrum disorder. This review highlighted the key role that environmental factors play as barriers and facilitators in the employment of people with autism spectrum disorder and the critical need for interventions which target contextual factors if employment outcomes are to be improved.